Iceberg: a loudspeaker-based room auralization method for auditory research - Aguirre, Sergio Luiz (2023)
Depending on the acoustic scenario, people with hearing loss are challenged on a different scale than normal hearing people to comprehend sound, especially speech. That happen especially during social interactions within a group, which often occurs in environments with low signal-to-noise ratios. This communication disruption can create a barrier for people to acquire and develop communication skills as a child or to interact with society as an adult. Hearing loss compensation aims to provide an opportunity to restore the auditory part of socialization. Technology and academic efforts progressed to a better understanding of the human hearing system. Through constant efforts to present new algorithms, miniaturization, and new materials, constantly-improving hardware with high-end software is being developed with new features and solutions to broad and specific auditory challenges. The effort to deliver innovative solutions to the complex phenomena of hearing loss encompasses tests, verifications, and validation in various forms. As the newer devices achieve their purpose, the tests need to increase the sensitivity, requiring conditions that effectively assess their improvements.